Determinants of real exchange rate movements in 15 emerging market economies (2019)
Previous work has established that an appreciation of the real exchange rate (REER) con-tributes to premature deindustrialization, less productive investment and dependence on commodity booms and busts in emerging markets economies (EME). From the literature, it is less clear, however, what the most important drivers for the cyclical REER movements in EME are. The main aim of this study is to provide empirical evidence about the determinants of the REER movements of 15 emerging markets during the last two decades, using statistical analysis and a dynamic panel fixed effects model approach. Our analysis shows that although “commodity” and “industrial” EME are heterogeneous, REER volatility tends to be higher among the former. Yet, REER volatility between emerging and advanced countries does not differ very much, apart from a few countries. EME that had more stable REER fared better than those that had a depreciating or appreciating trend (with the notable exception of China). As theoretically expected, commodity prices are an important structural driver of REER movements in “commodity EME”. Moreover, the results confirm the existence of the Harrod-Balassa-Samuelson effect, and show the importance of financial inflows. Further, the interventions of central banks were partially successful to avoid more substantial appre-ciations (depreciations). Finally, we find that lower country risk and, at least in some peri-ods, growing broad money in OECD countries has led to REER appreciations in our sample countries.